2020
DOI: 10.2196/23357
|View full text |Cite
|
Sign up to set email alerts
|

Using Character-Level and Entity-Level Representations to Enhance Bidirectional Encoder Representation From Transformers-Based Clinical Semantic Textual Similarity Model: ClinicalSTS Modeling Study

Abstract: Background With the popularity of electronic health records (EHRs), the quality of health care has been improved. However, there are also some problems caused by EHRs, such as the growing use of copy-and-paste and templates, resulting in EHRs of low quality in content. In order to minimize data redundancy in different documents, Harvard Medical School and Mayo Clinic organized a national natural language processing (NLP) clinical challenge (n2c2) on clinical semantic textual similarity (ClinicalSTS… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…It has often been reported that BERT exhibits high performance, even with clinical text [36][37][38][39]. This is also true for this study, in which a model combining BERT and Bi-LSTM using clinical text recorded in daily practice allowed for fall prediction with an accuracy equal to or higher than that of conventional risk assessment tools.…”
Section: Fall Prediction Model Performancesupporting
confidence: 66%
“…It has often been reported that BERT exhibits high performance, even with clinical text [36][37][38][39]. This is also true for this study, in which a model combining BERT and Bi-LSTM using clinical text recorded in daily practice allowed for fall prediction with an accuracy equal to or higher than that of conventional risk assessment tools.…”
Section: Fall Prediction Model Performancesupporting
confidence: 66%
“…We compare our results to existing methods and conduct ablation studies. Model N2C2STS (Xiong et al, 2020a) 0.868 (Ormerod et al, 2021) 0.870 (Chen et al, 2021) (single) 0.87 (Mulyar et al, 2021) 0.867 (Wang et al, 2022b) 0.875 EARA (BlueBERT) 0.887 across three benchmark datasets: N2C2STS, EBM-SASS, and BIOSSES. Notably, our approach consistently outperforms the baseline models, with average improvements ranging from 1.94% to 4.22%.…”
Section: Resultsmentioning
confidence: 99%
“…The first used data augmentation strategies (Wang et al, 2020c;Li et al, 2021a) or multi-task learning (Mulyar et al, 2021;Mahajan et al, 2020) to enhance the model's representation. The second introduced external knowledge into the neural network models, which can capture implicit information (Xiong et al, 2020a;Chang et al, 2021). These methods only integrate traditional features and lack interpretations.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation